Guest Editorial-SOLUTIONS OF CHILDHOOD OBESITY-AND-MALNUTRITION - Syed Arif Kamal (The Sky, 2022)
Childhood obesity and malnutrition have taken up prime importance for the medical community. This becomes much more important for the sport academies, who like to train and to groom national and international athletes. As early as the turn of this century, Ludwig (2007) discussed 4 phases of obesity pandemic, deliberating upon their long-term effects. Phase I, from 1970 till 2007, would have cases of obesity on rise due to lack of awareness of its damaging effects. After 2007, Phase II would appear with grave medical conditions as type-II diabetes, fatty lever and a number of psychosocial problems. In Phase III, the situation would, further, deteriorate and life-threatening diseases, like coronary heart disease, kidney failure and many more would increase mortality rate and shorten life expectancy of population of the United States. In Phase IV, the prevalence of weight-related diseases would accelerate more resulting in non-genetic influences in children, if such a trend continued. In an e-communication to Rafia Imtiaz (student of the author), Ludwig explained, “Phase IV of the epidemic would develop slowing over time, as obese children grow up and give birth to the next generation of children.” A year earlier, Collins et al. (2006) described programs for management of severe acute malnutrition in children.